State supervision, punishment and poverty: The case of drug bans on welfare receipt. (July 2021) - Sheely, Amanda
This article explores the relationship between supervisory approaches to governance, punishment, and poverty among people with drug convictions. Tying government assistance to supervision could improve employment and economic outcomes. However, if experienced as punishment, recipients may forgo financial assistance and be more likely to experience poverty. Using information on policies that restrict access to welfare for people with drug felony convictions in the Temporary Assistance to Needy Families (TANF) and the Supplementary Nutrition Assistance Programs (SNAP), this paper makes two contributions. First, it documents state variation in the balance between supervision and punishment in these bans. Second, using data from NLSY97, it estimates how individuals' likelihood of being in poverty is related to state SNAP drug ban policies. States have shifted away from overtly punitive policies denying access to welfare toward policies that increase supervisory requirements, especially for SNAP. This shows that punitiveness extends beyond work activation programs like TANF. Additionally, poverty among people with drug convictions is almost half in no ban states compared to those in full ban states. While poverty is lower in states that include supervisory requirements than in those for which a drug conviction fully blocks access to welfare, this difference was not statistically significant.